Dynamic color‐coded fluorescence imaging of the cell‐cycle phase, mitosis, and apoptosis demonstrates how caffeine modulates cisplatinum efficacy. Issue 11 (13th September 2013) - Miwa, Shinji; Yano, Shuya; Tome, Yasunori; Sugimoto, Naotoshi; Hiroshima, Yukihiko; Uehara, Fuminari; Mii, Sumiyuki; Kimura, Hiroaki; Hayashi, Katsuhiro; Efimova, Elena V.; Fujiwara, Toshiyoshi; Tsuchiya, Hiroyuki; et al.
ABSTRACT Caffeine enhances the effect of certain anticancer drugs, but the mechanism of modulation is poorly understood. In this study, modulation of cisplatinum efficacy induced by caffeine was visualized at the subcellular level by real‐time fluorescent‐protein imaging. Mitotic and apoptotic changes were observed by imaging 143B human osteosarcoma dual‐color cells, in which GFP is expressed in the nucleus and RFP is expressed in the cytoplasm. Modulation of the cell cycle was imaged using time‐lapse imaging of HeLa cells expressing a fluorescent ubiquitination‐based cell cycle indicator (FUCCI) in the nucleus. Clonogenic assays showed that caffeine increased the inhibition by cisplatinum on cell proliferation. Subcellular imaging demonstrated that cisplatinum decreased mitosis and induced apoptosis in 143B cells. The combination of cisplatinum and caffeine enhanced mitosis and subsequently increased apoptosis. Time‐lapse imaging showed that cisplatinum strongly induced cell‐cycle arrest in the S/G2 phase in HeLa‐FUCCI cells. Caffeine overcame the cell‐cycle arrest induced by cisplatinum, thereby increasing its efficacy, since cisplatinum is ineffective against quiescent cells. The data in this report indicate that caffeine modulates the cell cycle in cancer cells, thereby enhancing efficacy of cell‐cycle‐dependent anticancer drugs such as cisplatinum. J. Cell. Biochem. 114: 2454–2460, 2013. © 2013 Wiley Periodicals, Inc.